2017
DOI: 10.3390/ijms18020199
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Alterations of Hematopoietic Stem and Progenitor Cells in an In Vitro Leukemia-Induced Microenvironment

Abstract: An understanding of the cell interactions occurring in the leukemic microenvironment and their functional consequences for the different cell players has therapeutic relevance. By co-culturing mesenchymal stem cells (MSC) with the REH acute lymphocytic leukemia (ALL) cell line, we have established an in vitro leukemic niche for the functional evaluation of hematopoietic stem/progenitor cells (HSPC, CD34+ cells). We showed that the normal homeostatic control exerted by the MSC over the HSPC is considerably lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…MDP were the most communicative during disease progression with changes across many GO-BP for both ligands and receptors. Overall, our results support the notion that the leukemia BMM can alter the activities of HSPCs 36 .…”
Section: Discussionsupporting
confidence: 88%
“…MDP were the most communicative during disease progression with changes across many GO-BP for both ligands and receptors. Overall, our results support the notion that the leukemia BMM can alter the activities of HSPCs 36 .…”
Section: Discussionsupporting
confidence: 88%
“…We have recently established an in vitro leukemic niche (LN) model to simulate BM cell interactions and to study functional alterations of HSC in a leukemic microenvironment [14, 24]. In the present work, we found that leukemic cells induce MSC senescence by a p53-mediated pathway and ROS production.…”
Section: Introductionmentioning
confidence: 56%
“…Many studies have shown that during leukemia proliferation, the hematopoietic niche is remodeled, altering its properties by mechanisms that are only partially understood, but may include abnormal expression of cell adhesion molecules, aberrant migration capacity, and secretion of soluble factors, among others [912]. It is believed that these changes improve the survival and proliferation of leukemic cells in the niche [13] to the detriment of HSC [10, 14]. Specifically, the information related to MSC alterations in the leukemic microenvironment, and the molecular mechanisms involved, is scarce with some exceptions in AML and CML [1518].…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow (BM) stromal cells, in particular mesenchymal stem cells (MSC) play a pivotal role in cellular homeostasis within the BM microenvironment not only in physiological but also in pathological conditions [1]. Cross-talk between MSC and leukemic cells has reciprocal functional consequences [2,3], and also in surrounding cells, with overwhelming consequences [4,5]. The relevance of this interaction for the leukemic cells is evidenced by the fact that despite the upregulation of antiapoptotic genes, primary leukemic cells are in general incapable of surviving ex vivo without a cell stromal support, and need to be co-cultured with for example BM-MSC [6,7].…”
Section: Introductionmentioning
confidence: 99%